A Analisa Usability Website BAKTI-Kemkominfo Menggunakan System Usability Scale - Ali Farzah; Oktaviana, Shinta (MULTINETICS, 2022)
BAKTI is a government organization in a Public Service Agency under the Ministry of Communication and Information. A total of 2,485 website visitors are recorded during October. In contrast to the Ministry of Communications and Informatics Legal Bureau website, which reached an average of 24,896 visitors in October. Some menus repeat to the home page, and there are no service product details, causing disinformation on the BAKTI website. The research aims to overview the value of the usability level, acceptance, and quality level of the BAKTI website. The System Usability Scale (SUS) method assesses acceptance or usability by considering the low cost, small sample, and relatively short time with adequate results. The result of calculating the SUS score for the BAKTI website is 71.40. It shows the acceptance level of the BAKTI website at Marginal High, the quality level at level C, and the usability level at the "OK" level. The assessment results for the BAKTI website indicate the need to improve the website by referring to the effects of research instruments. The results of the 4th and 8th instruments, around 19-32%, show that the website is not yet user-friendly because respondents still find it difficult and still need the help of technical people when browsing the website. Then on the 5th and 6th instruments, around 23-35% of respondents' assessments show that there are still impaired functions on the website and the need for content improvement to eliminate inconsistencies when browsing the BAKTI website.